Antropometri Kelahiran terhadap Kejadian Stunting di Desa Tentenan Barat, Kabupaten Pamekasan - Fauzatur Rofiqoh; Eny Qurniyawati; Annis Catur Adi (Universitas Airlangga, 2024)
Background: According to the 2022 data, 21.6% of Indonesian children under the age of five suffer from stunting, which is still below the 2024 RPJMN target. Pamekasan is one of the priority regency for stunting in Indonesia. Birth anthropometry, such as birth length and weight, are some of the risk factors for stunting. Hence, it is essential to conduct research at the village level to examine these risk factors and continue to reduce the stunting incidence in the future. Objectives: This study aim to analyze the association between birth anthropometry (birth length and weight) and stunting. Methods: This study was an analytic observational study using a case-control approach. The research was carried out in Tentenan Barat Village, Pamekasan Regency, Madura, East Java Province. The type of data in this research was secondary data obtained from ePPBGM data at Larangan Community Health Center in February 2023. The number of samples used in this study was 54 (18 cases and 36 controls). Analysis of the relationship between dependent and independent variables using the Fisher Exact test. Results: Birth weight was not correlated with stunting (p-value = 0.107). Birth length was related to stunting (p-value = 0.012; OR = 8.5; 95% CI= 1.506 < OR < 47.962). Conclusion: Birth length was birth anthropometry that associated with stunting in this study. It is necessary to fulfill nutritional intake and provide health care for mothers, especially during pregnancy, to prevent children from being born with low body weight and short length.